Analisis pengungkapan modal intelektual: Perbandingan antara universitas di Indonesia dan Malaysia - Ihyaul Ulum; Malinda Malik; Hafiez Sofyani (Jurnal Ekonomi dan Bisnis, 2019)
This study aims to identify the Intellectual Capital (IC) disclosure practices of Indonesia and Malaysian universities on their official websites. This study used ten websites of best Indonesia and Malaysian universities based on 4ICU (International Colleges and Universities) 2018. The Modal intellectual framework developed by Leitner (2004) was used. The framework consists of 36 items: 10 human capital items, nine structural capital items, dan 17 relational capital items. Mann-Whitney U (non-parametric based) was used to test the hypothesis. The result shows that there was a difference between Indonesia and Malaysian universities about the level of Modal intellectual disclosure on their official websites. Generally, the percentages of IC information disclosed on Indonesia and Malaysian universities’ website is just about 50%, while the rest is undisclosed. This indicates that the awareness of the university’s management toward IC disclosure is still low. Therefore, the government role in improving the practice of IC disclosure through regulatory instruments is recommended.